Moral Message-Based Deep Learning in Mathematics Instruction for Mathematics MGMP Teachers of Kubu Raya - Basuni, Bistari; Mikraj, Hamdani; Rustam, Rustam; Ahmad, Dian; Zubaidah, Zubaidah; Winarji, Agus; Nurfadilah, Nurfadilah; Pasaribu, Revi Lestari; Jamilah, Jamilah; Junarti, Junarti (STKIP Singkawang, 2025)
The seminar titled